The ability of video games to depict cancer as a dramatic experience. A comparative study with literature and cinema (Communication & Society, 2019)
Given that the democratisation of video games has allowed this industry to appropriate a series of themes traditionally the exclusive preserve of other expressive media, this work analyses the capacity of videoludic expression to elicit emotions and convey the seriousness of cancer by performing a comparative study with literature and cinema. To this end, three works (one per medium) were selected to be respectively read, viewed or played by all the study subjects (n=90). A two-step methodology was employed. Firstly, the concepts of emotion and narrative scheme were defined in the context of disciplines relating to the three media and then shared with the subjects. Secondly, once both variables, i.e. the concepts of emotion and narration, had been controlled, a questionnaire was designed to determine which of the three works comprising the corpus best conveyed the experience of cancer. The results reveal that the sample game, in spite of its shortcomings in character design, was judged to be the one that most poignantly described the development of the disease. Therefore, it is possible to claim that the common belief that video games are trivial devices, solely designed to entertain, contrasts with their true expressive ability to convey dramatic experiences.